Peasant uprising in seventeenth-century France, Russia and China. Transl. from the French by B. Pearce (Allen & Unwin, 1971)
With ill., index and maps. Original title: Fureurs pausannes: les paysans dans les révoltes du XVII siècle (France, Russie, Chine).